PENERAPAN TANGGUNG RENTENG PADA KELOMPOK SIMPAN PINJAM PEREMPUAN - Ramdani, Ramdani (Jurnal Al-Amwal, 2018)
The implementation of the share responsibility is one of the efforts to minimize the occurrence of bad credit in the management of revolving fund loans at Activity Management Unit at Padakembang Sub-district. The share responsibility cannot work without the participation of group members, the level of participation will determine the application of the share responsibility is running or not. This research is descriptive research with a qualitative approach. The technique of collecting data uses two sources, namely primary sources and secondary sources, primary sources are obtained through interviews with sources and secondary sources are obtained through financial reports and loan progress reports. The results showed that the application of share responsibility at Activity Management Unit at Padakembang Sub-district was well marked by a letter of willingness to share responsibility, the inclusion of collateral in the form of submission and the existence of group savings of 10% of the loan whose signature specimens involved management as controls to these savings. In terms of group members participation in capital participation and utilization of business services were good, social capital was developed in screening prospective members and utilization of business services, although not yet at the group. Access to group members loans to Activity Management Unit at Padakembang Sub District sureached 100%. The conclusion of this study shows that the implementation of share responsibility in Activity Management Unit at Padakembang Sub-district tends to formality, this occurs because the groups that appear are not due to unifying ties but rather to efforts to access loans. Different things were found in the participation of their members who were enthusiastic in terms of participation even though participation in the organizational sector was still weak due to the absence of group rules.